Bridging the Translational Gap in Heart Failure Research: Using Human iPSC-derived Cardiomyocytes to Accelerate Therapeutic Insights - Leslye Venegas-Zamora; Matthew Fiedler; William Perez; Francisco Altamirano (Methodist DeBakey Cardiovascular Journal)
Heart failure (HF) remains a leading cause of death worldwide, with increasing prevalence and burden. Despite extensive research, a cure for HF remains elusive. Traditionally, the study of HF’s pathogenesis and therapies has relied heavily on animal experimentation. However, these models have limitations in recapitulating the full spectrum of human HF, resulting in challenges for clinical translation. To address this translational gap, research employing human cells, especially cardiomyocytes derived from human-induced pluripotent stem cells (hiPSC-CMs), offers a promising solution. These cells facilitate the study of human genetic and molecular mechanisms driving cardiomyocyte dysfunction and pave the way for research tailored to individual patients. Further, engineered heart tissues combine hiPSC-CMs, other cell types, and scaffold-based approaches to improve cardiomyocyte maturation. Their tridimensional architecture, complemented with mechanical, chemical, and electrical cues, offers a more physiologically relevant environment. This review explores the advantages and limitations of conventional and innovative methods used to study HF pathogenesis, with a primary focus on ischemic HF due to its relative ease of modeling and clinical relevance. We emphasize the importance of a collaborative approach that integrates insights obtained in animal and hiPSC-CMs-based models, along with rigorous clinical research, to dissect the mechanistic underpinnings of human HF. Such an approach could improve our understanding of this disease and lead to more effective treatments.